Protective effects and network analysis of natural compounds obtained from Radix dipsaci, Eucommiae cortex, and Rhizoma drynariae against RANKL-induced osteoclastogenesis in vitro. (15th November 2019) - Cheng, Chi-Fung; Chien-Fu Lin, Jeff; Tsai, Fuu-Jen; Chen, Chao-Jung; Chiou, Jian-Shiun; Chou, Chen-Hsing; Li, Te-Mao; Lin, Ting-Hsu; Liao, Chiu-Chu; Huang, Shao-Mei; Li, Ju-Pi; Lin, Jung-Chun; et al.
Abstract: Ethnopharmacological relevance: Osteoporosis is one of the most common bone diseases; it is characterized by bone loss and is a risk factor for hip fracture. Chinese herbal medicines (CHMs) and their related natural compounds have been used for treating many diseases, including bone diseases, since ancient times in China and are regarded as a cost-effective complementary therapy. Aim of the study: The goal of this study was to investigate the osteoprotective mechanisms of these three Chinese herbs and their related natural compounds. The effects of CHMs and related natural compounds on RANKL-induced osteoclastogenesis in vitro were investigated. Materials and methods: A network pharmacology method was applied to study CHM-related natural compounds and their osteoporosis targets. In addition, their effect on RANKL-induced osteoclastogenesis in RAW264.7 cells was also investigated in vitro . Results: Radix dipsaci, Eucommiae cortex, and Rhizoma drynariae exhibited protective effects against mortality in hip fracture patients. Furthermore, these three herbs inhibited RANKL-induced TRAP activities and reduced the expression of bone resorption-related genes in RAW264.7 cells. Network analysis of natural compound (ingredient)-target interactions identified 11 natural compounds. Signal pathway analyses suggested that these compounds may target cytokine-cytokine receptor interactions, including RANKL-induced osteoclastogenesis. Five novel natural compounds exhibited reduced RANKL-induced TRAP activities and bone resorption-related gene expression. Conclusion: The clinically used CHMs, Radix dipsaci, Eucommiae cortex, and Rhizoma drynariae, and natural compounds obtained from them may suppress RANKL-induced osteoclastogenesis in vitro . Graphical abstract: Image 1